2023
DOI: 10.1039/d3py00434a
|View full text |Cite
|
Sign up to set email alerts
|

Capsules with responsive polymeric shells for applications beyond drug delivery

Yifei Wang,
Nicholas Starvaggi,
Emily Pentzer

Abstract: Polymeric capsules with core-shell structures have been widely explored for molecule separations, energy storage, and catalysis, among other applications. To tailor the application-oriented performance of these structures, researchers have imparted...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Our group has demonstrated that encapsulation of ILs overcomes various limitations involved in process design. Specifically, we prepared capsules with a core of IL and GO/polymer composite shell by interfacial polymerization in Pickering emulsions. , As a proof of concept that encapsulation is beneficial to fluorinated gas absorption, FIL-4 was encapsulated and utilized for HFC gas uptake. Encapsulation of the FILs was achieved through interfacial polymerization within a nonaqueous Pickering emulsion template (Figures A and S5A), producing capsules with a core of FIL and shell of polyurea and GO nanosheets.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has demonstrated that encapsulation of ILs overcomes various limitations involved in process design. Specifically, we prepared capsules with a core of IL and GO/polymer composite shell by interfacial polymerization in Pickering emulsions. , As a proof of concept that encapsulation is beneficial to fluorinated gas absorption, FIL-4 was encapsulated and utilized for HFC gas uptake. Encapsulation of the FILs was achieved through interfacial polymerization within a nonaqueous Pickering emulsion template (Figures A and S5A), producing capsules with a core of FIL and shell of polyurea and GO nanosheets.…”
Section: Resultsmentioning
confidence: 99%
“…Hollow polymer particles are used in various industrial fields as light scattering agents and thermal insulation owing to their unique physical properties. , Furthermore, capsule particles prepared by functional molecules encapsulated into hollow polymer particles enable broader applications, such as biomedicals, , cosmetics, micro/nanoreactors, , and self-healing agents . Additionally, fabrication approaches for hollow and capsular particles, such as the template-assisted approach, have been widely developed, in which a polymer shell layer is formed on sacrificial templates (e.g., Au, SiO 2 , and CaCO 3 ) by seeded polymerizations, layer-by-layer, , and surface-initiated (photo)­polymerizations. Ge et al developed polyelectrolyte microcapsules by the layer-by-layer approach with microbubbles as templates .…”
Section: Introductionmentioning
confidence: 99%
“…5 Encapsulation imparts thermal stability to the core, resistance to leakage, and enhanced protection against undesired reactions with external agents. 6 Additionally, encapsulation resolves challenges with bulk active liquid processing (e.g., high viscosity) and increases the active surface area, which may assist in the mass transfer of small molecules across the interface. 7 Most commonly, encapsulation may be accomplished via hard-template approach, wherein a polymer shell is grown around a sacrificial core (e.g., layer-by-layer assembly atop a silica particle), 8 or via soft-template approach, which utilizes a stable biphasic system (e.g., interfacial polymerization in emulsions).…”
Section: Introductionmentioning
confidence: 99%
“…5 Encapsulation imparts thermal stability to the core, resistance to leakage, and enhanced protection against undesired reactions with external agents. 6 Additionally, encapsulation resolves challenges with bulk active liquid processing ( e.g. , high viscosity) and increases the active surface area, which may assist in the mass transfer of small molecules across the interface.…”
Section: Introductionmentioning
confidence: 99%